Increasing Production Through Local Potency-Based Feed Formulations as Alternatives to Artificial Feeds in Catfish Farming - Suryanto Hertika, Asus Maizar; Nurlaelih, Euis Elih; Shofwan, Shofwan; Putra, Renanda Baghaz Dzulhamdani Surya; Alfarisi, Muhammad Asnin (Journal of Innovation and Applied Technology, 2024)
Doktor Mengabdi (DM) engages in collaborative efforts to address the issue of escalating feed costs, which result in minimal profits or even financial losses. This is intensified if, during the harvest period, the price of catfish per kilogram decreases. The imperative to address these issues is subsequently addressed through training in the development and production of self-sustaining animal feed utilizing the capabilities of indigenous components. The BUMDES of Labruk Lor Village and the "Mina Agung Mandiri" Fish Farming Group collaborated with the Lumajang District Fisheries Service to carry out the activity. The applied results for this activity encompass: 1) fostering social interaction and promoting comprehension among activity partners; 2) providing guidance and education to enhance understanding of effective and proper fish farming techniques, as well as enabling the production of fish feed using readily available local resources; and 3) implementing the process of fish feed production, which involves grinding the raw materials, blending the various components, and utilizing a fish feed pellet printing machine for shaping. 4). Assessment and surveillance of the execution of tasks 5). Assessing the effects of actions, including their impact on the economy and the growth of fish, This activity empowers farmers to produce feed autonomously and demonstrates a significant upsurge of up to 40% in the profitability of fish farming operations. Moreover, the measurements conducted suggest that the water quality in each partner's pond remains appropriate for the growth of fish and does not exhibit any signs of diseases that could hinder the cultivation and development of the fish.